A new bent-toed gecko (Squamata: Gekkonidae: Cyrtodactylus) from the Western Himalayas, Himachal Pradesh, India - Agarwal, Ishan; Khandekar, Akshay; Bauer, Aaron M. (Zootaxa, 2018)
We describe a new species of the gekkonid genus Cyrtodactylus based on a series of six specimens from the Chamba Valley in the Western Himalayas, Himachal Pradesh state, India. Cyrtodactylus chamba sp. nov. is a member of the subgenus Siwaligekko and can be diagnosed from congeners in the Western Himalayas by a combination of its small size (snout to vent length up to 63 mm), a continuous series of five precloacal pores on males, 13–15 rows of dorsal tubercles, 33–43 scales across the belly, no regular series of enlarged subcaudals, and a dorsal colour pattern of 5–7 irregular, broad, dark bands with much narrower, light interspaces. The new species is 14% divergent in ND2 sequence from the most similar sampled congener, Cyrtodactylus (Siwaligekko) himalayanus from Jammu and Kashmir, and is 0.5–1.1% divergent in nuclear sequence data from sampled Siwaligekko species. Many more undiscovered Cyrtodactylus species probably exist across the Himalayas at elevations below ~2000 m; basic field surveys for reptiles and other poorly known groups and examination of existing material should be a priority if we are to appreciate the true diversity of this spectacular mountainous landscape.